Experimental and numerical analysis of Carbon/Glass fiber reinforced thermoplastic wind turbine blade prepared by VARIM - H N Abhilash; K Raghunandana; Subraya Krishna Bhat; Aruna Prabhu; A Amar Murthy (Materials Research Express)
The output of wind energy, a vital renewable resource, has increased from 94 GW to 591 GW globally in the last ten years. Weight and cost are important considerations in wind turbine blade (WTB) design, as rotor blades make up 40%–80% of the overall weight, to fulfill the growing need for energy. Even though thermosetting composites are frequently used to make blades, they have several drawbacks, most notably that they cannot be recycled. As more blades approach the end of their lives and become unreformable once cured, recycling and disposal become more difficult, and environmental concerns increase. The main objective of the present work is to manufacture thermoplastic composites reinforced with fibers using the Vacuum Assisted Resin Infusion Moulding (VARIM) technique and assess their mechanical characteristics. The finite element analysis of the WTB incorporates the material parameters calculated for the thermoplastic resin. Test coupons are produced by shaping thermoplastic resin and fiber reinforcement using VARIM. The mechanical characteristics, including flexural and impact strength, are then assessed utilizing destructive testing techniques. Thermoset resins have good flexural properties while thermoplastic resins have better impact properties. The wind turbine blade (WTB) is simulated in ANSYS ACP based on the designated stacking sequence and fiber orientation. Static structure analysis is performed for the thermoplastic and thermosetting composites under various operating circumstances. Identification and analysis of the critical section susceptible to mechanical failure are conducted under different loading conditions, and the obtained outcome is verified. Based on the results, it is concluded that thermoplastic composites are viable materials for manufacturing wind turbine blades.